T cell receptor-independent immunosuppression induced by dexamethasone in murine T helper cells. - Sierra-Honigmann, M R (1992)
The immune and inflammatory responses are largely inhibited by glucocorticosteroids. In thymocytes, for example, glucocorticosteroids cause apoptosis, whereas they suppress the activity of phospholipase A2 and the production of eicosanoids in tissues actively engaged in inflammation. The immunosuppressive action of dexamethasone (DEX) was studied in vitro by employing a model cell system, namely the murine Th2 clone D10.G4.1 (D10) and its clonotypic anti-T cell receptor (TCR) mAb 3D3. Although the proliferative response of D10 cells to 3D3 stimulation was not affected by DEX, the costimulation provided by IL-1 was dramatically inhibited. Substitution of 3D3 by exogenous IL-4 (as the IL-1 costimulant) failed to prevent the inhibition of proliferation caused by DEX. Yet, when 3D3-mediated stimulation of TCR was supplemented with IL-2, D10 cells were capable of proliferating, even in the presence of DEX. Thus, TCR stimulation on D10 cells remained intact and their resulting propagation was not compromised by DEX treatment. These results provide evidence that immunosuppression caused by DEX is TCR independent and involves an early cytokine-signalling event.